2003
DOI: 10.1007/s00240-003-0331-4
|View full text |Cite
|
Sign up to set email alerts
|

Tumor type M2 pyruvate kinase expression in metastatic renal cell carcinoma

Abstract: The M2 isoenzyme of pyruvate kinase (M2-PK) is specifically expressed in tumor cells (TuM2-PK) and has been detected in the peripheral blood of patients with renal cell carcinoma (RCC). TuM2-PK is not useful as a biological marker in localized RCC. We analysed TuM2-PK in 68 patients with metastatic RCC after initial surgery and prior to or during chemoimmunotherapy of metastases. In 50 patients, the levels of TuM2-PK were measured during chemoimmunotherapy with interleukin-2, interferon-alpha2a and 5-fluoroura… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
6
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 7 publications
2
6
0
Order By: Relevance
“…In the present study on OSCC, the median TuM2-PK concentration of the tumour group was 22.92 U/ml compared with 10.00 U/ml in the control group (Fig. 1), which is in accordance with results previously reported by various authors for other malignancies (Varga et al, 2002;Roigas et al, 2003;Ventrucci et al, 2004;Zhang et al, 2004). The test failed to discriminate between the two groups despite the highly significant difference between the median TuM2-PK concentration in the tumour and control groups (p\ 0.001).…”
Section: Discussionsupporting
confidence: 95%
See 1 more Smart Citation
“…In the present study on OSCC, the median TuM2-PK concentration of the tumour group was 22.92 U/ml compared with 10.00 U/ml in the control group (Fig. 1), which is in accordance with results previously reported by various authors for other malignancies (Varga et al, 2002;Roigas et al, 2003;Ventrucci et al, 2004;Zhang et al, 2004). The test failed to discriminate between the two groups despite the highly significant difference between the median TuM2-PK concentration in the tumour and control groups (p\ 0.001).…”
Section: Discussionsupporting
confidence: 95%
“…The small tumour mass of OSCC, even in stage T4, could be a possible explanation for the findings of this study. However, the results are in agreement with Varga et al (2002), Hegele et al (2003), Oremek et al (2003b), Roigas et al (2003) and Staib et al (2006) who have found similar sensitivities and specificities for other malignancies and suggested that the TuM2-PK test was unsuitable for monitoring and early detection of cancer.…”
Section: Discussionsupporting
confidence: 90%
“…Furthermore, elevated plasma PK-M2 was found in higher stage of ovarian cancer [31] and was correlated with poorly differentiated periampullary cancer [32]. However, dysregulation of either LDH or PK-M2 was not proved as a prediction factor for the response to chemotherapy [33].…”
Section: Discussionmentioning
confidence: 99%
“…8 Finally, the glycolytic enzyme pyruvate kinase M2 is expressed in most human tumors. 9, 10, 11, 12 This enzyme typically exists in its less active, dimeric form in cancers due to the actions of various oncoproteins as well as post-translational modifications. 13, 14, 15, 16 Collectively, all of these diverse actions function to block the flux through glycolysis.…”
Section: Introductionmentioning
confidence: 99%